Physical Activity and Rehabilitation - Yuling WANG (康复学报)
Objective:To explore the mechanism and responses of physical activity on neurological, musculoskeletal, and cardiopulmonary system etc., and elaborate the efficacy of physical activity intervention and the foundation of rehabilitation management.Methods:We searched the database of PubMed, Ovid, and Elsevier via the key words on physical activity, exercise, mechanism, and rehabilitation, summarized and reviewed the relevant topics and results of selected studies.Results:There were large amounts of researchs which based on quantitative and individualized protocol in the clinical rehabilitation focused on the influence and responses on various body systems. Many studies indicated that positive and negative responses during the exercise intervention on neurological, musculoskeletal, and cardiopulmonary system.Conclusion:Exercise and physical activity are the active rehabilitation interventions and essential elements of our daily living either from the clinical rehabilitation practice or from the health care requirements. Exercise is a good medicine which needs the scientific design and individualized protocol and also a healthy behavior habit.